2013
DOI: 10.1071/ch13209
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Structures of Group 12 and 14 Element Halide–Carbene Complexes

Abstract: The synthesis of a series of N-heterocyclic carbene (NHC) complexes involving zinc, cadmium, and the heavy Group 14 elements germanium, tin, and lead is reported. The direct reaction between the bulky carbene IPr (IPr = (HCNDipp)2C:, Dipp = 2,6-iPr2C6H3) and the Group 14 halide reagents GeCl4 and SnCl4 afforded the 1 : 1 complexes IPr·ECl4 (E = Ge and Sn) in high yield; similarly, ZnI2 interacted with IPr in THF to give the THF-bound complex IPr·ZnI2·THF. CdCl2 underwent divergent chemistry with IPr and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Adducts 1a – c are highly soluble in THF but moderately soluble in aromatic hydrocarbons. The 1 H NMR spectra of 1a – c in [D 6 ]benzene are similar and exhibit the typical pattern for the IMes ligand coordinated to zinc , . In the 13 C{ 1 H} NMR spectra, the zinc‐bound carbene signals appear at δ = 174.0 ( 1a ), and 177.1 ( 1b and 1c ) ppm.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Adducts 1a – c are highly soluble in THF but moderately soluble in aromatic hydrocarbons. The 1 H NMR spectra of 1a – c in [D 6 ]benzene are similar and exhibit the typical pattern for the IMes ligand coordinated to zinc , . In the 13 C{ 1 H} NMR spectra, the zinc‐bound carbene signals appear at δ = 174.0 ( 1a ), and 177.1 ( 1b and 1c ) ppm.…”
Section: Resultsmentioning
confidence: 73%
“…It is important to note that 1a – c contain variable quantities of THF as 1a – c·(THF) 0–1 unless rigorously dried. IPr‐bonded [(IPr)ZnI 2 ] was similarly isolated and crystallized from THF as [(IPr)ZnI 2 (thf)], whereas solvent‐free [(IPr)ZnBr 2 ] 2 was synthesized from toluene and crystallized as a dimer from benzene (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…One year later, the group of Rivard described the IDipp adduct of GeCl 4 ( 755 ) obtained in a straightforward reaction, by mixing the two components in diethyl ether (Figure ). This compound can be reduced to the donor–acceptor-stabilized germylene 756 , which will be discussed later …”
Section: Nhc Complexes Of Main Group Elementsmentioning
confidence: 85%
“…Rivard et al reported on the (IDipp)­SnCl 4 adduct ( 839 ), which is isostructural to the germanium congener 755 (vide supra) . It contains a trigonal bipyramidal-coordinated tin atom with the C NHC –Sn bond length of 2.186 Å, which compares well to 837c .…”
Section: Nhc Complexes Of Main Group Elementsmentioning
confidence: 95%
“…However, it is worthwhile to give an indication of the broad areas of the field that are covered by the authors. Aspects of low oxidation state main group chemistry and ligand design are covered by Driess, [9] Goicoechea, [10] Jones, [11] Rivard, [12] Stasch, [13] and Weigand. [14] The application of main group compounds to synthetic methods is addressed in papers by Coles, [15] Driess, [9] Dutton, [16] Mulvey, [17] Scheschkewitz, [18] and Westerhausen.…”
mentioning
confidence: 99%